SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PENYELEKSIAN CALON KARYAWAN PADA PT.WKS MENGGUNAKAN METODE PROFILE MATCHING: Decision Support System;Employees;Profile Matching;MySQL;PHP. - Afrizal; Santoso, Budi (LP2M Universitas Nurdin Hamzah, 2022)
Wirakarya Sakti (WKS) is a company that produces timber from plantations that are prepared to be managed as industrial materials for factories. Where is PT. Wirakarya Sakti grows quality wood that has been selected, in the process of planting or collecting until harvest. This Decision Support System (SPK) application uses the profile matching method which was created to assist PT. Wirakarya Sakti in conducting the best employee assessment process by considering intelligence, work attitude and behavior. The purpose of this research is to make it easier and easier to select prospective employees by getting the best employees. The process of this application where prospective employees only need to take part in interviews and tests by getting scores and processed by ranking the target value from the calculation (SPK) with the profile matching method. Input data is employee data generated from the achievement value of prospective employees while the output is in the form of employee ranking reports. This application is made using the PHP Framework Igniter script and uses a MySQL database.